Priority-Based Charging Technique for Multiple Port Dc Electric Vehicle Charger - Espina-Gonzalez, E; Diaz-Diaz, M; Toledo-De la Garza, K (Institute of Electrical and Electronics Engineers Inc., 2024)
The increasing demand for Electric Vehicles (EVs) has underscored the need to develop charging infrastructure. Traditional fast charger topologies, such as the Dual Active Bridge, only support charging one vehicle at a time and lack flexibility in terms of modularity and scalability in voltage and power. Recently, Modular Multilevel Converters have been proposed as a potential solution to address these limitations in high-power EV charging applications. This paper presents a control strategy for a Series-Parallel Modular Multilevel Converter based EV charger. This strategy considers a priority-based charging strategy to redistribute power according to each EV priority and maximum power capability. Furthermore, it allows for bidirectional power flow, providing Vehicle-to-Grid capability. Simulation results are presented using a simplified series-parallel modular multilevel converter model developed in PLECS to validate the performance of the proposed control strategy. © 2024 IEEE.